2021
DOI: 10.1080/07853890.2021.1916069
|View full text |Cite|
|
Sign up to set email alerts
|

Pioglitazone improves skeletal muscle functions in reserpine-induced fibromyalgia rat model

Abstract: Background: Fibromyalgia (FM) is characterized by musculoskeletal pain, fatigue, sleep and memory disturbance. There is no definitive cure yet for FM-related health problems. Peroxisome proliferator-activated receptor's (PPAR's) activation is associated with insulin sensitisation and improved glucose metabolism. PPAR-c was reported to alleviate FM allodynia. Limited data are discussing its effect on motor disorders. Objective: To investigate the potential effect of PPAR-c agonists (pioglitazone, as one member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…Treating fibromyalgia (multisystem failure process involving the immune, musculoskeletal, and central nervous system ) in rats with PPAR-γ agonist, pioglitazone resulted in a significant improvement of skeletal muscle functions, reduced fatigability, and rapid recovery from fatigue [49], which is consistent with our results. Blocking the PPAR-γ pathway, though administration of GW9662, counteracted pioglitazone's protective effects [49]. Interestingly, experimental studies have also shown a reduction in the level of peroxisome proliferatoractivated receptor-gamma coactivator (PGC-1α), one of the proteins activated by PPAR-γ in skeletal muscles of HD mice models as well as HD patients [50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Treating fibromyalgia (multisystem failure process involving the immune, musculoskeletal, and central nervous system ) in rats with PPAR-γ agonist, pioglitazone resulted in a significant improvement of skeletal muscle functions, reduced fatigability, and rapid recovery from fatigue [49], which is consistent with our results. Blocking the PPAR-γ pathway, though administration of GW9662, counteracted pioglitazone's protective effects [49]. Interestingly, experimental studies have also shown a reduction in the level of peroxisome proliferatoractivated receptor-gamma coactivator (PGC-1α), one of the proteins activated by PPAR-γ in skeletal muscles of HD mice models as well as HD patients [50].…”
Section: Discussionsupporting
confidence: 91%
“…Although PPAR-γ expression in skeletal muscle and the heart is relatively small, there are studies indicating that these receptors may play an important role in its metabolism and function [47,48]. Treating fibromyalgia (multisystem failure process involving the immune, musculoskeletal, and central nervous system ) in rats with PPAR-γ agonist, pioglitazone resulted in a significant improvement of skeletal muscle functions, reduced fatigability, and rapid recovery from fatigue [49], which is consistent with our results. Blocking the PPAR-γ pathway, though administration of GW9662, counteracted pioglitazone's protective effects [49].…”
Section: Discussionsupporting
confidence: 90%
“…The top primary hit was calcitriol (1,25(OH)2D3) or the bioactive form of vitamin D3 (Figure 1E). Pioglitazone, one of the other primary hits, has been shown to be a PPARg agonist that significantly improved skeletal muscle functions in a reserpine‐induced fibromyalgia rat model 27 . Another primary hit, cholecalciferol, is an inactive precursor of calcitriol which requires sequential hydroxylation in the liver and then the kidney before it binds avidly to the vitamin D receptor, 28 and has also been shown to improve muscle strength and performance in athletes and old adults 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Pioglitazone, one of the other primary hits, has been shown to be a PPARg agonist that significantly improved skeletal muscle functions in a reserpine-induced fibromyalgia rat model. 27 Another primary hit, cholecalciferol, is an inactive precursor of calcitriol which requires sequential hydroxylation in the liver and then the kidney before it binds avidly to the vitamin D receptor, 28 and has also been shown to improve muscle strength and performance in athletes and old adults. 29,30 The identification of pioglitazone and cholecalciferol as positive hits further supported the validity of our primary screening and data analysis, although the identification of both calcitriol and cholecalciferol despite their vastly different K d 's for VDR (3.8 pM and >20 mM, respectively) also suggested that VDRindependent mechanisms might be operating.…”
Section: Identification Of Natural Compounds That Promote Muscle Volu...mentioning
confidence: 99%
“…The results of recent meta-analyses of population studies indicate that PIO efficiently decreases the blood pressure, the level of triglycerides, glycated hemoglobin, and blood glucose in fasting animals, as well as the risk of hypoglycemia [ 2 , 3 , 4 ]. Besides, due to its anti-inflammatory, antioxidant, and, perhaps, antibacterial and antifungal properties, PIO is now considered as a promising medicine for the treatment of a range of pathologic states, including Alzheimer’s disease [ 5 ], depressive disorder [ 6 ], non-alcoholic fatty liver disease [ 7 ], renal ischemia-reperfusion injury [ 8 ], Klebsiella pneumoniae infection [ 9 ], fibromyalgia-associated motor dysfunctions [ 10 ], respiratory infections (including Coronavirus disease 2019) [ 11 , 12 ], chronic obstructive pulmonary disease [ 13 ], cryptococcal meningitis [ 14 ], and ischemic outcomes induced by mild traumatic brain injury [ 15 ]. The intake of PIO is associated with a decrease in carotid intima-media thickness, a hallmark of atherosclerosis progression [ 2 , 16 ].…”
Section: Introductionmentioning
confidence: 99%